The Effect of Corporate Diversification on Firm Value: In the Presence of Financial Crisis - Li, Zhi (2016)
This paper examines the value of corporate diversification during 2001 and 2015. Analysis of firms’ excess value with differences-in-differences model reveals a significant diversification discount over the pre-crisis period while it turns to positive after the crisis. The value increased in diversified firms becomes significant since the model is corrected for self-selection issues. However, I do not find the evidence on the hypothesis that the same relationship between diversified firms and focused firms would remain for unrelated and related diversifiers. Therefore, I propose that the value of firm may not necessarily link to the degree of diversification, suggesting diversifiers should strike a balance between diversification and specialization especially for the year of recession.